Design of a compact reconfigurable antenna with triple band switchable characteristics - Pardhasaradhi, P; T.P. Madhav, B; Rajendra Kamal, D; Chinna Somaiah, M; Gayathri, Ch; Koteswara Rao, M; Anilkumar, T (International Journal of Engineering and Technology, 2017)
Antennas with reconfigurable functionality is the mostly preferred one in the antennas field. In such scenario, a work is presented in this article proposing a frequency reconfigurable antenna with a compact PIFA kind of structure. The antenna structure has the folded radiating structure and embedded with some lumped resistance and distributed capacitance, inductance for providing the impedance matching across desired bands for wireless communication. Further, the switching elements (PIN diodes-BAR64-02V) are inserted in the gap between the long-meandered line structure for attaining the switchable characteristics among single band (0.68-0.98 GHz), dual band (0.70 – 0.96 GHz, 2.26 - 2.65 GHz), and triple band (0.69 - 0.99 GHz, 1.89 - 2.78 GHz, 3.64 – 4.1 GHz) respectively. The impedance bandwidth is considered according to S11 < -6 dB criteria for the mobile communication applications. The proposed antenna is suitable for smartphone, laptop and portable devices with GSM/PCS/WCDMA/UMTS/LTE communication applications.